Coronary Artery Bypass Graft for Left Main Coronary Artery Disease - Husain H. Jabbad, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Because left main coronary artery disease carries a high risk of morbidity and mortality, this retrospective study will review the data and results of surgical management of left main coronary artery disease, in King Abdulaziz University Hospital. 448 patients underwent coronary bypass graft into two groups, left main group (50) patients and non-left main group (398) patients. Preoperative data, risk factors and cardiac catheterization findings were compared in between the two groups in addition to perioperative morbidity and mortality. Patients in the left main group were younger in age with significantly lower ejection fraction and more risk factors (hypertension, dyslipidemia, and smoking). In our study the left main group patients had higher mortality than non-left main patients [4 patients = 8%, 6 patients = 1.8%]; the most common cause of perioperative mortality in the left main group was low cardiac output state, and the most common complications were perioperative myocardial infarction and prolonged ventilation. The higher mortality and morbidity associated with surgery for left main coronary artery disease can be explained by the higher risk profi le, the need of urgent surgery and critical preoperative status.